The impact of unplanned 30-day readmission as a quality indicator in pediatric surgery - Ellul, Sarah; Shoukry, Mohamed (Frontiers in Surgery, 2023)
Introduction Hospital readmission is one of the indicators used to assess quality of service provided in healthcare. Based on accumulated knowledge, risk management teams assess data related to readmissions to find curative solutions for underlying factors. The current article’s aim is investigating readmission routes within the workplace in paediatric surgery service during the first 30 days post discharge from Mater Dei Hospital (MDH). Materials and Method A retrospective study of children’s hospital readmissions between October 2017 and November 2019 was performed, strictly before COVID-19 pandemic. Demographics and clinical records including age, gender, pre-existing comorbidities, diagnosis during primary admission and readmission, procedure carried out, ASA grade, length of stay, and outcomes were collected. All children re-admitted under a single paediatric surgical department within 30 days from initial admission to tertiary referral hospital were included. Patients undergoing emergency visitation without subsequent admission were excluded. Readmissions were classified into cohorts: elective and emergency, depending on nature of primary admission. Contributing factors and outcomes were compared. Results 935 surgical admissions (221 elective and 714 emergencies) were registered at MDH over the given period, with an average hospital stay of 3.62 days. Total readmission rate was 1.7% (n=16). 25% (n=4) of readmissions were post elective, 75% (n=12) post emergency admission, with an average stay of 4.37 days and no mortalities. 43.7% (n=7) were re-admissions post-surgical intervention. Further surgical interventions were necessary in 25% (n=4) of readmitted patients, remainder (n=12) treated conservatively. Conclusion Published reports concerning paediatric surgical readmission rates are limited, challenging healthcare systems. Most readmissions area voidable; therefore, healthcare workers must provide adequate strategies tailored to their resources, efficient multidisciplinary approaches with improved communication to decrease morbidity and prevent readmissions.